Can Gender Moderate the Effect of Digital Learning Media and Interest on Learning Outcomes? - Kurniawan, Muchammad Akbar; Julaihah, Umi; Bashith, Abdul; Amin, Saiful; Dewi, Sari (Journal of Education on Social Science (JESS), 2025)
The purpose of this study is to analyse the effect of digital learning media and learning interest on learning outcomes based on gender. This study uses a quantitative approach with Structural Equation Modelling (SEM) through Multi-Group Analysis (MGA), involving 254 students from Madrasah Tsanawiyah in Singosari, Malang, to measure the effect of digital learning media and student learning interest on learning outcomes. The results of structural test showed that neither digital learning media nor learning interest had a significant effect on learning outcomes, and gender did not moderate the relationship. Further, based on PLS-MGA, it is found that gender did not moderate the relationship in the model. Suggestions for future research include exploring the relationship between students' learning styles and the use of learning media, conducting longitudinal studies to evaluate the long-term impacts of digital learning media on outcomes, and considering factors such as personality, motivation, and age differences as moderating variables to gain a more comprehensive understanding of their effects on student learning outcomes.